Empowerment of Fishermen Communities Amidst Elite Interest Conflicts: A Study on the Implementation of Integrated Cold Storage Policy in Jember, Indonesia - R., Emy Kholifah; Widagdo, Suwignyo; Nusanto, Baktiawan (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
This study examines the complexities surrounding the Empowerment of coastal communities amidst conflicting elite interests, mainly focusing on the political-economic dynamics of cold storage management in Puger Kulon, Jember Regency. Utilizing descriptive qualitative research methods, data were gathered from coastal community leaders, local government officials, and fishermen. The findings reveal significant challenges stemming from cultural and economic factors in empowering coastal communities. The presence of interest groups seeking to maintain influence exacerbates these challenges. The power struggle between politically influential figures and external investors leaves the community disadvantaged. While the government aims to maintain regional stability, its limited authority impedes effective action. The inability to implement large-scale empowerment initiatives or delegate responsibilities due to a high conflict of interest among entrepreneurs hampers efforts to enhance fishermen's welfare.